Catch of the Decade : How to Launch, Build and Sell a Digital Business - Leibovich, Gabby; Leibovich, Hezi (Wiley, 2021)
"Gabby and Hezi were always the most looked-up-to duo in ecommerce and they truly taught me how to trade!' Nick Molnar, CEO, Afterpay 'The Leibovich brothers are pioneers of Australian ecommerce. You cannot afford to not read this book.' Christine Holgate, Group Chief Executive Officer & Managing Director, Australia Post 'Real stories and advice from'digital entrepreneurs'who have learned what it takes to succeed In'Catch of the Decade, 'two of Australia's most successful online superstars reveal how they've built, launched, merged, 'and sold some of the most disruptive businesses in Australia today: Catch, 'Scoopon, 'Menulog'and Luxury Escapes.'This book contains'little-known secrets and strategies that will help you'shorten'your learning curve, avoid mistakes, 'and'bring your business dream alive.' The wisdom revealed in this book is hard won: brothers'Gabby and'Hezi'Leibovich started'with no money'and'no connections, turned their'drawbacks into assets, and came out on top.'You'll learn how they rode'the waves of entrepreneurialism'and worked their way up.' -Learn proven tips to define, disrupt and dominate a sector or industry, straight from'entrepreneurs who achieved their billion-dollar dreams.-Read hard hitting, no bull'nuggets of'wisdom'in the areas of customer service, PR, Buying and trading, engaging investors and more.-Market-tested strategies for building big brands, creating high-performing teams and fostering a world-class entrepreneurial culture. For the first time, 'the'Leibovich'brothers are telling their story, 'in their own'words, and you'll learn how they got where they are today. Follow in their footsteps with over 200'bite-sized'entries'that are both inspirational and useful.'Pick up'Catch of the Decade'and get moving!"